2013
DOI: 10.1111/1756-185x.12135
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with rheumatoid arthritis in Qatar: a cross-sectional study

Abstract: Sixty-four percent of rheumatoid arthritis patients in Qatar were in remission or had low disease activity while the remaining 36% had active disease and among these patients 29% were on biologics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…Badsha et al5 reported patients from the United Arab Emirates to have a mean DAS 28 of 5.2, and 12% of their patients were in the low disease activity or remission categories. In another regional study by Lutf et al,6 findings were different from our study in a heterogeneous group of patients with RA. Their mean DAS 28 was 2.85, 49% were in remission, and an additional 15% were in the low disease activity category 6…”
Section: Discussioncontrasting
confidence: 99%
“…Badsha et al5 reported patients from the United Arab Emirates to have a mean DAS 28 of 5.2, and 12% of their patients were in the low disease activity or remission categories. In another regional study by Lutf et al,6 findings were different from our study in a heterogeneous group of patients with RA. Their mean DAS 28 was 2.85, 49% were in remission, and an additional 15% were in the low disease activity category 6…”
Section: Discussioncontrasting
confidence: 99%
“… 2 Patients in these countries are also often undertreated 5 , 16 and there is wide variation in treatment, with 5% of patients in the United Arab Emirates (UAE) and 29% in Qatar receiving a biologic, compared with over 40% of eligible patients in the USA. 19 In part, this can be attributed to the high socioeconomic burden of other more prevalent diseases in the Middle East and Arabian Gulf countries, such as diabetes. 15 Public awareness regarding RA is also generally low in the region, but data from the UAE show that the introduction of patient support groups and disease awareness campaigns are beginning to show an effect.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 15 In Qatar, the majority of patients receive conventional synthetic (cs) DMARDs, and 64% of patients seen in the clinic achieve LDA or remission. 19 Yet despite this move towards modern practice, RA patients often experience a delay in diagnosis: a recent study in Dubai found erosions in 55% of patients, suggesting a delay in diagnosis and management. 16 A review examining the use of the European League Against Rheumatism (EULAR) recommendations in this region found that there were barriers to implementation, mainly for those individual recommendations that advocated aggressive management, early use of intensive therapy and frequent monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…In a multicenter cross-sectional study of RA in Chinese patients receiving csDMARDs, bDMARDs, and/or glucocorticoids, Wang et al found the remission rate to be 8.6 % (DAS28), 8.2 % (CDAI), 8.4 % (SDAI), and 6.8 % (Boolean) [27]. In Qatari, the remission rate of patients with RA receiving bDMARDs and/or csDMARDs was 49 % by DAS28 score [28]. In the QUEST-RA study including patients with RA from 25 mostly European countries, remission rate was 13.8 % and 19.6 % by CDAI and DAS28, respectively [29].…”
Section: Discussionmentioning
confidence: 99%